The Effect of Group Reminiscence Therapy on Insomnia in Older Adults: A Randomized Controlled Clinical Trial - Fatemeh Sahragard; Mahboubeh Rezaei; Fatemeh Sadat Izadi-Avanji; Fatemeh Atoof; Maryam Ahmadishad (Golestan University of Medical Sciences, 2020)
Background: Insomnia is one of the common sleep disorders in the elderly. Lack of adequate sleep has many consequences, such as fatigue, frustration and increased rate of mortality among them. The study was carried out to determine the effect of group reminiscence therapy on insomnia in older adults. Methods: This randomized controlled clinical trial was done on 72 older adults who referred to Sadoughi health care center in Kashan, Iran between August and November 2018.The subjects were recruited through convenience sampling and randomly allocated into two control and intervention groups. The reminiscence therapy was held twice a week, in a 4-week period for intervention group and the duration of each session varied between 1.5-2 hours. There was no intervention in control group. Data were collected using Mini-Mental State Examination (MMSE), and Insomnia Severity Index (ISI). Data was gathered three times; before intervention, immediately and one month after the intervention. Data were analyzed using Chi-Square, and Man-Whitney tests and repeated measures analysis in SPSS (v. 16.0, SPSS Inc., Chicago, IL, USA). Results: The mean score of insomnia decreased in intervention group after group reminiscence therapy (p<0.001); from 16±1.74 (before the intervention) to 11.27±2.09 (immediately after the intervention) and 11.38±1.93 (one month after the intervention), while the insomnia score had not noticeable change in control group. The intervention group showed significantly less insomnia scores over the time compared to control group (p < 0.05). Conclusions: Reminiscence therapy decreases the severity of insomnia in older adults. Therefore, it can be used as an easy, applicable and low-cost technique in health care facilities and is expected to be welcomed by older adults, their families and health care providers.